Clinical Profile of Patients with Seizure in Kathmandu Medical College Teaching Hospital. - Dhungana, Krishna; Shakya, Dipesh; Shrestha, Rabindra; Bhatta, Sabnam; Maharjan, Sabbu (Journal of Nobel Medical College, 2019)
Background: Seizure is a common clinical condition. It represents a majority of patients visiting neurology OPD as well as inpatient department in Kathmandu Medical College Teaching Hospital. While the number of patients with seizure is increasing in Nepal, data on the clinical profile of patients with seizure is scarce. Thus, this study aims to find out the relative frequency of seizure in different age and sex groups. It also aims to find out the common causes of seizure in our Nepalese population. Materials and Methods: A descriptive cross sectional study was carried out in patients attending outpatient and inpatient of Neurology department of Kathmandu Medical College Teaching Hospital between periods of July 2018 to December 2018. Demographic characteristics, radiographic findings, EEG findings and drugs taken by patients were recorded according to the proforma. Results: Data from one hundred patients were collected and analyzed. Most of the patients were less than 41 years of age. Most of the patients were male. The prime cause of seizure was found to be neurocysticercosis (25%). Majority of the patients were on monotherapy. Conclusion: Our data regarding the frequency of seizure in different age and sex groups is comparable to data in South East Asia region whilst, different from the western data. In our population, neurocysticercosiswas the most common cause of seizures. Also, most seizures were controlled with monotherapy.